Pengaruh Pendidikan Kewirausahaan Terhadap Intensi Berwirausaha Melalui Minat Berwirausaha Sebagai Variabel Moderasi Pada Mahasiswa FEB UNESA - Trista, Vienna Eka; Dwi Yuli Rakhmawati (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
In an effort to achieve the Visi Indonesia Emas 2045, various policies have been issued, one of it is the development of entrepreneurship education in higher education where FEB UNESA is one of the institutions that implements it. However, data from the tracer study shows that the entrepreneurial intention of FEB UNESA alumni is low. This study aims to analyze the influence of entrepreneurship education on entrepreneurial intention through entrepreneurial interest as a moderating variable in FEB UNESA students. The data in this study were obtained from the process of distributing questionnaires to 380 students which were then analyzed using SmartPLS 4 software. The results of this study are that entrepreneurship education has no effect on entrepreneurial intentions, entrepreneurial interest has an effect on entrepreneurial intentions, and entrepreneurial interest can moderate the effect of entrepreneurship education on entrepreneurial intentions.